2001
DOI: 10.1111/j.1365-2745.2001.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Tree mortality rates and longevity in mature and old‐growth hemlock‐hardwood forests

Abstract: 1 Efforts to understand and forecast long-term forest dynamics are often hindered by limited data on mortality rates and longevity of trees in older stands. In this study, mortality data were analysed from 11-year permanent plot records in 10 tracts of hemlock-hardwood forest with little past human disturbance in the upper Great Lakes region, USA.2 We compared tree size-mortality trends in mature stands (canopy trees mostly 100-170 years old) with those in true old-growth stands (canopy trees mostly 200-350 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 45 publications
8
62
0
1
Order By: Relevance
“…Stem mortality rates (for trees 15 cm dbh) are within the range -but clustered at the low end -of turnover rates (average of recruitment and mortality) reported in a review of studies in 27 conifer forests (Stephenson and van Mantgem 2005). Mortality rates in the present study were similar to, but generally slightly lower than, those reported for other old-growth conifer forests (van Mantgem et al 2009) in western North American and old-growth mixed hemlock (T. canadensis) -hardwood forests in eastern North America (Lorimer et al 2001;Busing 2005).…”
Section: Forest-wide Species-and Size-specific Mortality Ratessupporting
confidence: 83%
See 2 more Smart Citations
“…Stem mortality rates (for trees 15 cm dbh) are within the range -but clustered at the low end -of turnover rates (average of recruitment and mortality) reported in a review of studies in 27 conifer forests (Stephenson and van Mantgem 2005). Mortality rates in the present study were similar to, but generally slightly lower than, those reported for other old-growth conifer forests (van Mantgem et al 2009) in western North American and old-growth mixed hemlock (T. canadensis) -hardwood forests in eastern North America (Lorimer et al 2001;Busing 2005).…”
Section: Forest-wide Species-and Size-specific Mortality Ratessupporting
confidence: 83%
“…This logic culminated in the prediction that in old-growth forests, a Ushaped curve would describe the relationship of tree mortality rate to tree diameter at breast height. Since then, several investigators have searched for the U-shaped mortality curve, with varying degrees of support (e.g., Runkle 2000;Lorimer et al 2001;Coomes et al 2003).…”
Section: Forest-wide Species-and Size-specific Mortality Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate decreases first and subsequently increases with the increased tree DBH in nonkarst forests [62][63][64][65][66][67]. Small trees are in a weak position when competing for illumination, nutrition, and spatial resources; they are also vulnerable to diseases and pests [68].…”
Section: Discussionmentioning
confidence: 99%
“…As a simplified approach, mortality has been generally considered either as regular, due to competition or ageing, or as irregular, caused by ecological and catastrophic events, such as storm or fire (Monserud 1976). The probability of regular mortality is believed to be U-shaped, indicating relatively high mortality rates for small and large trees due to light competition and senescence, respectively (Monserud & Sterba 1999, Lorimer et al 2001, Fraver et al 2008. The probability of irregular mortality is rather fluctuating, and thus quite difficult to predict, since it may be triggered by various biotic and abiotic factors, which change temporally and spatially, e.g., the attack of pests or diseases may cause a comparatively small mortality in one year, or eliminate the host species from the region ( Vanclay 1994).…”
Section: Introductionmentioning
confidence: 99%